2006
DOI: 10.13181/mji.v15i1.214
|View full text |Cite
|
Sign up to set email alerts
|

Non-dirt house floor and the stimulant of environmental health decreased the risk Acute Respiratory Infection (ARI)

Abstract: Beberapa faktor terkait dengan infeksi saluran napas atas (ISPA) antara lain lantai rumah. Tujuan penelitian adalah untuk mengetahui dampak program kesehatan keluarga dan gizi (KKG) dan beberapa faktor risiko yang lain yang berkaitan dengan ISPA. Data berasal dari survey yang dilakukan di 5 provinsi di Indonesia, pada projek KKG pada tahun 2003. Subjek terdiri dari 1.500 keluarga yang dipilih dengan cara stratifikasi random. Interview dan observasi ke rumah subjek dilakukan oleh petugas yang terlatih khusus un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Ten factors reduced the risk of ARI in toddlers. They were permanent floor types, permanent walls, lighting, existence of a clean water source, closed and clean garbage dumps, septic tank distance over 10 m, throwing the garbage in its place, a closed sewage channel, having an absorbing well, distance between the garbage dump and the clean water source over 10 m. The results of this study are in line with the research results of Suriyasa et al 20 They found that non-dirt floors decreased ARI incidence by 51% compared with dirt house floor. The research of Cardoso et al 15 also supported that cases of respiratory illnesses would arise when the house did not meet the physical requirements (construction types, building materials, measurement of the floor area, wall height, windows, and solar orientation) and did not have adequate waste disposal.…”
Section: Discussionsupporting
confidence: 90%
“…Ten factors reduced the risk of ARI in toddlers. They were permanent floor types, permanent walls, lighting, existence of a clean water source, closed and clean garbage dumps, septic tank distance over 10 m, throwing the garbage in its place, a closed sewage channel, having an absorbing well, distance between the garbage dump and the clean water source over 10 m. The results of this study are in line with the research results of Suriyasa et al 20 They found that non-dirt floors decreased ARI incidence by 51% compared with dirt house floor. The research of Cardoso et al 15 also supported that cases of respiratory illnesses would arise when the house did not meet the physical requirements (construction types, building materials, measurement of the floor area, wall height, windows, and solar orientation) and did not have adequate waste disposal.…”
Section: Discussionsupporting
confidence: 90%